The demographic situation in Peru - Gonzáles Díaz, Violeta (2015)
While, in what participants to this conference Population, may concern, this is only a partial approach called population problem, it will also be a basic condition scientific knowledge of the population of Peru, within the context clearly population. Thus any set of measures to influence the behavior of demographic variables, fertility, mortality, migration, should from this knowledge. Who attended the meetings of Population in Tarma, made in June, have had the opportunity to hear that Peruvian demographers have been criticized by professionals from other disciplines, not having given population issues its true dimension, and perhaps not been sufficiently influential to an awareness of population issues.